Electric power systems resiliency : modelling, opportunity and challenges - Mishra, Manohar; Sood, Yog Raj; Bansal, Ramesh C. (Academic Press, 2022)
Electric Power Systems Resiliency: Modelling, Opportunity and Challenges considers current strengths and weaknesses of various applications and provides engineers with different dimensions of flexible applications to illustrate their use in the solution of power system improvement. Detailing advanced methodologies to improve resiliency and describing resilient-oriented power system protection and control techniques, this reference offers a deep study on the electrical power system through the lens of resiliency that ultimately provides a flexible framework for cost-benefit analysis to improve power system durability.